Prevalence of Some Heavy Metals, Physicochemical Parameters and Pesticide Residues in Water and Soil of River Nukkai Jalingo Taraba State, Nigeria - Modibbo U.U; Andekun Andrew, Hassan; Usman Y. M, (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2024)
Pesticides residues and heavy metals contaminants became threats with alarming effects on ecosystem around River Nukkai in Jalingo, Taraba State were human activities discharge pesticides residues and heavy metals within the environment. The study was aimed to ascertain the concentrations of heavy metals in the water and soil using Atomic Absorption Spectrometry (AAS) and the concentrations of pesticide residues in water and soil using GC-MS. The result revealed marked variations of distribution of the physicochemical parameters from all the three sampling sites of the River Nukkai. pH, temperature, EC, TDS, and TSS have values that fall below the WHO and USEPA permissible limit for drinking water with exception of turbidity (119.03 mg/l). The mean concentration of heavy metals examine in water and soil at sampling points revealed are; Zn (0.06 mg/L), Cu (0.15 mg/L), Pb (0.10 mg/kg), Cd (0.07 mg/kg), Zn (22.27 mg/kg), Cu (3.27 mg/kg), and Cr (2.98 mg/kg) determined in water and soil respectively were within international safe limits while Cd (0.03 mg/l), Pb (0.04 mg/l) and Cr (0.39 mg/l) levels in water are beyond (0.003, 0.01 and 0.05mg/l) USEPA safer limits required for clean water. Within the seven sampling points, total of 13 pesticides were analyzed in both water and soil samples at the area. The concentration of pesticides in sampling sites of river Nukkai, ranged from RNI = 0.039649 mg/L to 3.37558 mg/L, RNM = 0.013662 mg/L to 0.92898 mg/L, and RNO = 0.118807 mg/L to 8.27369 mg/L respectively. While the concentration of pesticides in sampling sites of agricultural soil around river Nukkai banks, ranged from RNSN = 0.017585 to 25.5124, RNSE = 0.100216 to 47.1208, RNSS = 0.214391 to 31.6663, and RNSW = 0.029031 to 27. 9176 mg/kg respectively. Methoxychlor and P, P’ -DDE are the predominant contaminants of water while Aldrin and Alpha-lindane are the major contaminants of soils. It was also observed that all the pesticide residues and heavy metals concentration detected at the area are beyond the Maximum Residue Limits set for drinking water and agricultural soils, due to excess utilization of pesticides by the citizens of the area.